Influence of Mulching on Plant Growth Performance in Young Plantation Plots on Coal Mine Spoil - Jha, Arvind Kumar; Singh, Arvind; Singh, A. N.; Singh, J. S. (Indian Forester, 2001)
Plantation of Dendrocalamus strictus was raised on coal mine spoil at Jayant project, NCL, Singrauli in June 1993. Half and full dose of NPK fertilizer was applied. Full dose of NPK fertilizer was nitrogen as urea (60 kg ha-1), phosphorus as single superphosphate (30 kg ha-1) and potash as muriate of potash (40 kg ha-1). Half dose of NPK treatment increased the height growth more whereas full dose of NPK treatment enhanced markedly the number of culms/clump and diameter growth of D. strictus.